2013
DOI: 10.7567/jjap.52.04cg15
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Properties of Rare-Earth-Doped Thiosilicate Phosphors on Silicon Substrate

Abstract: The luminescence properties of rare-earth-doped thiosilicate phosphors are reported. These thiosilicate materials are fabricated in phosphor layers on silicon substrates. For Eu2+-doped calcium thiosilicate, yellow (560 nm) and red (650 nm) bands are obtained in the photoluminescence spectrum, which is almost the same as that for the corresponding powder sample. The energy transfer efficiency from Eu2+ to Er3+ in Eu2SiS4:Er3+ on Si substrates is improved by optimization of the annealing conditions. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A disappointing feature of this phosphor is that it requires high temperatures and reducing atmosphere to produce. On the other hand, thiosilicate phosphors also have multiple substitution sites and can be fabricated at a relatively low temperature [15][16][17][18][19][20][21]. Especially, we have confirmed that the monoclinic (Gd,Ce) 4 (SiS 4 ) 3 and (Y,Ce) 4 (SiS 4 ) 3 show broad luminescence originated from Ce 3+ ions replaced with multiple Y or Gd sites in Y 4 (SiS 4 ) 3 and Gd 4 (SiS 4 ) 3 [20].…”
Section: Introductionsupporting
confidence: 62%
“…A disappointing feature of this phosphor is that it requires high temperatures and reducing atmosphere to produce. On the other hand, thiosilicate phosphors also have multiple substitution sites and can be fabricated at a relatively low temperature [15][16][17][18][19][20][21]. Especially, we have confirmed that the monoclinic (Gd,Ce) 4 (SiS 4 ) 3 and (Y,Ce) 4 (SiS 4 ) 3 show broad luminescence originated from Ce 3+ ions replaced with multiple Y or Gd sites in Y 4 (SiS 4 ) 3 and Gd 4 (SiS 4 ) 3 [20].…”
Section: Introductionsupporting
confidence: 62%
“…Up to now, silicate, silicon nitride, silicon oxynitride, and thiosilicate materials have been reported. [17][18][19][20][21][22][23][24][25][26][27][28][29] In particular, thiosilicate phosphors have the advantage that a relatively low temperature is necessary for fabrication, and various luminescence wavelengths from blue to infrared have been reported. 17,[21][22][23][24][25][26][27][28][29] From these viewpoints, the fabrication of a visible and infrared thiosilicate phosphor is expected.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29] In particular, thiosilicate phosphors have the advantage that a relatively low temperature is necessary for fabrication, and various luminescence wavelengths from blue to infrared have been reported. 17,[21][22][23][24][25][26][27][28][29] From these viewpoints, the fabrication of a visible and infrared thiosilicate phosphor is expected. In this research, we discovered a new Ce 3+ -activated CaY 2 Si 2 S 8 thiosilicate phosphor, which crystallizes in the Ce 2 PbSi 2 S 8 (ref.…”
Section: Introductionmentioning
confidence: 99%